Association between labor duration in transvaginal deliveries and the risk of neonatal intensive care unit admission for newborns - Chen, Huajuan; Zhou, Chunyi; Yan, Xiaomeng; Shao, Hui (Frontiers in Pediatrics, 2025)
ObjectiveTo investigate the relationship between the duration of the first and second stages of labor and the risk of neonatal admission to the neonatal intensive care unit (NICU) among women undergoing vaginal delivery, with the aim of optimizing labor duration to mitigate adverse neonatal outcomes.MethodsA retrospective study was conducted to analyze baseline data from 13,480 singleton mothers and newborns who underwent vaginal delivery at a tertiary maternity hospital in Zhejiang Province between January 2021 and December 2023. Propensity score matching (PSM) was utilized to adjust for 12 confounding factors that could influence adverse neonatal outcomes, excluding the durations of the first and second stages of labor. Both stages of labor were categorized into quartiles. Single-factor and multifactor logistic regression analyses were performed before and after PSM to investigate the relationship between labor duration and the risk of neonatal NICU admission. Additionally, multi-model logistic regression analyses further examined this relationship. Restricted cubic spline (RCS) plots were generated before and after PSM to assess any non-linear associations between the durations of the first and second stages of labor and NICU admission risk. Subgroup analyses were also conducted to explore how labor duration impacts NICU admission risk across different population segments.ResultsOut of 13,480 neonates, 763 were admitted to the NICU. Multi-model logistic regression analyses indicated that longer durations of the second stage of labor, both before and after matching, were positively associated with an increased risk of NICU admission. In contrast, longer first stage labor durations did not correlate with higher admission risk. Additionally, the RCS analysis revealed a nonlinear relationship between the duration of the second stage of labor and the risk of neonatal NICU admission. Subgroup analyses confirmed that extended second stage labor duration was linked to the risk of NICU admission across various population segments.ConclusionWithin a certain range, a longer duration of the second stage of labor was associated with an increased risk of neonatal NICU admission. However, no significant correlation was found between the duration of the first stage of labor and the risk of neonatal NICU admission.